Impaired mitochondrial respiration in large cerebral arteries of rats with type 2 diabetes - Merdzo, Ivan (J Vasc Res, 2017)
Mitochondrial dysfunction has been suggested as a potential underlying cause of pathological conditions associated with type 2 diabetes (T2DM). We have previously shown that mitochondrial respiration and mitochondrial protein levels were similar between the large cerebral arteries of insulin resistant Zucker obese rats and their lean controls. In the present study we extended our investigations into mitochondrial dynamics of the cerebral vasculature of 14 week old Zucker diabetic fatty obese rats (ZDFO) with early T2DM. Body weight and blood glucose levels were significantly higher in the ZDFO group, and basal mitochondrial respiration and proton leak were significantly decreased in the large cerebral arteries of the ZDFO rats compared with lean controls (ZDFL). The expression of mitochondrial proteins total MnSOD and VDAC were significantly lower in the cerebral microvessels, and the acetylated MnSOD levels were significantly reduced in large arteries of ZDFO group. Additionally, superoxide production was significantly increased in the microvessels of the ZDFO group. Despite evidence of increased oxidative stress in ZDFO, exogenous superoxide dismutase was not able to restore mitochondrial respiration in ZDFO rats. Our results show for the first time that mitochondrial respiration and proteins levels are compromised during the early stages of T2DM.